TRADISI DAN TEKNOLOGI: STRATEGI KOMUNIKASI SOSIALISASI ANALOG SWITCH OFF (ASO) TELEVISI MELALUI PERTUNJUKAN RAKYAT - Budhipradipta, Citra Meidyna (Institut Seni Budaya Indonesia Bandung, 2023)
ABSTRACT This article reviews the communication strategies employed by the Ministry of Communication and Information Technology (Kominfo) in promoting the policy transition from analog to digital television in Indonesia. This transition process, known as Analog Switch Off (ASO), represents a crucial step in the development of broadcasting technology in Indonesia. However, ASO also faces various challenges, including resistance from some segments of the population. The research methodology involves desk study and literature review, based on official reports from Kominfo regarding the ASO communication campaign and relevant literature in the fields of public communication and social behavioral change communication. The findings from the study indicate that Kominfo has utilized a cultural and storytelling approach as the primary tools in communicating social and behavioral change to address public resistance. This approach integrates local cultural values, regional languages, and cultural humor in folk art performances tailored to the cultural characteristics of different regions in Indonesia and vividly depicts the benefits of using Digital TV. This article underscores the importance of understanding and leveraging cultural capital in developing successful communication strategies to achieve desired social and behavioral changes while merging cultural traditions with technological innovation. ABSTRAK Artikel ini mengulas strategi komunikasi yang digunakan oleh Kementerian Komunikasi dan Informatika (Kominfo) dalam sosialisasi kebijakan transisi dari televisi analog ke televisi digital di Indonesia. Proses peralihan ini, dikenal sebagai Analog Switch Off (ASO), merupakan langkah penting dalam pengembangan teknologi siaran di Indonesia. Namun, ASO juga menghadapi berbagai tantangan, termasuk penolakan dari sebagian masyarakat. Metodologi penelitian ini melibatkan desk study dan tinjauan literatur, berdasarkan laporan resmi Kominfo terkait kampanye komunikasi ASO dan literatur relevan di bidang komunikasi publik dan komunikasi perubahan perilaku. Temuan dari studi menunjukkan bahwa Kominfo telah menggunakan pendekatan budaya dan storytelling sebagai alat utama dalam komunikasi perubahan sosial dan perilaku untuk mengatasi tantangan penolakan publik. Pendekatan ini memadukan nilai-nilai budaya lokal, bahasa daerah, dan humor kebudayaan dalam pertunjukan kesenian rakyat yang disesuaikan dengan karakteristik budaya setiap daerah di Indonesia dan menggambarkan manfaat penggunaan TV Digital secara hidup dan menarik. Artikel ini menggarisbawahi pentingnya memahami dan memanfaatkan modal budaya dalam mengembangkan strategi komunikasi yang sukses untuk mencapai tujuan perubahan sosial dan perilaku yang diinginkan, sambil menggabungkan tradisi budaya dengan inovasi teknologi.